Single bout of vibration-induced hamstrings fatigue reduces quadriceps inhibition and coactivation of knee muscles after anterior cruciate ligament (ACL) reconstruction - Yu, S.; Lowe, T.; Griffin, L.; Dong, X. N. (Journal of Electromyography and Kinesiology, 2020)
Persistent quadriceps strength deficits in individuals with anterior cruciate ligament reconstruction (ACLr) have been attributed to arthrogenic muscle inhibition (AMI). The purpose of the present study was to investigate the effect of vibration-induced hamstrings fatigue on AMI in patients with ACLr. Eight participants with unilateral ACLr (post-surgery time: M=46.5, SD=23.5months; age: M=21.4, SD=1.4years) and eight individuals with no previous history of knee injury (age: M=22.5, SD=2.5years) were recruited. A fatigue protocol, consisting of 10min of prolonged local hamstrings vibration, was applied to both the ACLr and control groups. The central activation ratio (CAR) of the quadriceps was measured with a superimposed burst of electrical stimulation, and hamstrings/quadriceps coactivation was assessed using electromyography (EMG) during isometric knee extension exercises, both before and after prolonged local vibration. For the ACLr group, the hamstrings strength, measured by a load cell on a purpose-built chair, was significantly (P=0.016) reduced about 14.5%, indicating fatigue was actually induced in the hamstrings. At baseline, the ACLr group showed a trend (P=0.051) toward a lower quadriceps CAR (M=93.2%, SD=6.2% versus M=98.1%, SD=1.1%) and significantly (P=0.001) higher hamstrings/quadriceps coactivation (M=15.1%, SD=6.2% versus M=7.5%, SD=4.0%) during knee extension compared to the control group. The fatigue protocol significantly (P=0.001) increased quadriceps CAR (from M=93.2%, SD=6.2% to M=97.9%, SD=2.8%) and significantly (P=0.006) decreased hamstrings/quadriceps coactivation during knee extension (from M=15.1%, SD=6.2% to M=9.5%, SD=4.5%) in the ACLr group. In conclusion, vibration-induced hamstrings fatigue can alleviate AMI of the quadriceps in patients with ACLr. This finding has clinical implications in the management of recovery for ACLr patients with quadriceps strength deficits and dysfunction.